How Website Heatmap Software Can Be Used in Websites to Better Understand the User BehaviourHow Website Heatmap Software Can Be Used in Websites to Better Understand the User Behaviour - Ionut TANASE; Bianca Cristiana VOICU; Raluca-Giorgiana (POPA) CHIVU; Elena Florentina GREJDAN (Communications of International Proceedings, 2022)
Neuromarketing evaluates customer behaviour to marketing stimuli via research of the human brain. A heatmap is a website monitoring device that measures consumer interest on a webpage. A heatmap presents the descriptive statistics of attentiveness by superimposing a colour scheme pattern over the picture's features of interest. Analysis tools for websites have indeed been proven to be useful in a variety of areas. The information obtained from digital customer attitudes may be used to improve the content on websites, attract more customers and demand the consumer in their quest for material on webpages. Heatmapping give the company valuable client information, but it could also assist in addressing major website layout flaws that are obstructing the company's digital productivity.
Keywords: website heatmap; heatmapping; website user behaviour